The Effect of Psychodrama on the Empathy and Social Anxiety_x000D_ Level in Adolescents - (:unkn) unknown (My University, 2020)
Objectives: This study was conducted semi-experimentally to examine the effect of psychodrama on the level of social anxiety and empathy.Materials and Methods: The sample of the study consisted of nine volunteer students aged 13-17. The study took place between 05 March2002 and April 2018. Psychodrama sessions consisted of 10 sessions in total, 2 days a week. Empathic Tendency Adolescent scale and SocialAnxiety scale were used as data collection tools in the study.Results: When the total scores obtained from the Social Anxiety scale were examined, a statistically significant difference was found beforeand after psychodrama (p=0.029). When the total scores obtained from the Empathic Tendency scale were analysed, no statistically significantdifference was found. However, after psychodrama, there was an increase in the average score of the Empathic Tendency scale.Conclusion: Psychodrama is an effective method for reducing social anxiety and developing empathic skills in adolescents.

Amaç: Bu çalışma, psikodramanın sosyal kaygı ve empati düzeyine etkisini incelemek amacıyla yarı deneysel olarak yapılmıştır._x000D_ Gereç ve Yöntem: Çalışmanın örneklemini, 13-17 yaş aralığında yer alan dokuz gönüllü öğrenci oluşturmuştur. Çalışma 05 Mart - 02 Nisan_x000D_ 2018 tarihleri arasında gerçekleşmiştir. Psikodrama oturumları haftada 2 gün olmak üzere toplamda 10 oturumdan oluşmuştur. Çalışmada_x000D_ veri toplama aracı olarak Empatik Eğilim Ergen ölçeği ve Sosyal Kaygı ölçeği kullanılmıştır._x000D_ Bulgular: Sosyal Kaygı ölçeğinden alınan toplam puanlar incelendiğinde, psikodrama öncesi ve sonrası istatistiksel olarak anlamlı fark_x000D_ bulunmuştur (p=0,029). Empatik Eğilim ölçeğinden alınan toplam puanlar incelendiğinde ise, istatistiksel olarak anlamlı bir fark yoktur. Ancak_x000D_ psikodrama sonrasında Empatik Eğilim ölçeği puan ortlamasında artış olmuştur._x000D_ Sonuç: Psikodrama ergenlerde sosyal kaygının azaltılması ve empatik becerilerin gelişmesinde etkili bir yöntemdir._x000D_
Psikodramanın Ergenlerde Empati ve Sosyal Kaygı Düzeyine Etkisi